Prevalence of Burnout among University Students in Low- and Middle-Income Countries: A Systematic Review and Meta-analysis - Kaggwa, Mark Mohan; Kajjimu, Jonathan; Sserunkuma, Jonathan; Najjuka, Sarah Maria; Atim, Letizia Maria; Olum, Ronald; Tagg, Andrew; Bongomin, Felix (PloS one, 2021)
Burnout is common among university students and may adversely affect academic performance. Little is known about the true burden of this preventable malady among university students in low-and-middle-income countries (LMICs).This study aimed to systematically estimate the prevalence of burnout among university students in LMICs.We searched PubMed, Google Scholar, CINAHL, Web of Science, African Journals Online, and Embase from the inception of each database until February 2021. Original studies were included. No study design or language restrictions were applied. A random-effects meta-analysis was performed using STATA version 16.0. Heterogeneity and publication bias were assessed using Q-statistics and funnel plots, respectively.Fifty-five unique articles, including a total of 27,940 (Female: 16,215, 58.0%) university students from 24 LMICs were included. The Maslach Burnout Inventory (MBI) was used in 43 studies (78.2%). The pooled prevalence of burnout was 12.1% (95% Confidence Interval (CI) 11.9–12.3; I2 = 99.7%, Q = 21,464.1, p = < 0.001). The pooled prevalence of emotional exhaustion (feelings of energy depletion), cynicism (negativism), and reduced professional efficacy were, 27.8% (95% CI 27.4–28.3; I2 = 98.17%. p = <0.001), 32.6 (95% CI: 32.0–33.1; I2: 99.5%; p = < 0.001), and 29.9% (95% CI: 28.8–30.9; I2: 98.1%; p = < 0.001), respectively. Nearly one-third of university students in LMICs experience burnout. More studies are needed to understand the causes of burnout in this key population. There is a need to validate freely available tools for use in these countries.